Công văn của Thủ tướng Chính phủ về việc trả lời chất vấn của Đại biểu Quốc hội (Số: 1784/TTg-CN) - Thủ tướng Chính phủ (2017)
Công văn của Thủ tướng Chính phủ về việc trả lời chất vấn của Đại biểu Quốc hội (Số: 1784/TTg-CN) ngày 17/11/2017